Neoliberalism and the convergence of nonprofit care work in Canada. (June 2015) - Baines, Donna
Drawing on two different sets of qualitative interview and participant observation data collected in Canada in 2012 and 2013, this article asks why the social justice/nonprofit ethos operates differently within two subsectors of care work in the nonprofit sector, namely within long-term care and social services. The article argues that various similarities exist across the two highly gendered work forces such as resistance and care for services users. Models such as New Public Management may be compelling further convergence; however, certain differences remain as well. The data presented in the article sustained that, in these care work sectors, New Public Management is an uneven and gendered project, simultaneously resisted and sustained through the gendered self-exploitation of the workforce and the roots from which each subsector developed.